2008
DOI: 10.1111/j.1600-0838.2008.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of longstanding groin pain in athletes: a systematic review

Abstract: The aims of this study were to determine (1) the kinds of treatments applied for longstanding groin pain (LGP) in athletes; (2) the results; and (3) the levels of evidence for the interventions. Digital databases P were searched for articles describing the effects of interventions for LGP in athletes. Treatment of LGP in athletes can consist of conservative measures such as rest or restricted activity, active or passive physical therapy, steroid injections or dextrose prolotherapy. Studies describing surgery g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 57 publications
0
46
0
8
Order By: Relevance
“…A strain to the groin muscles may be acute but often becomes chronic in nature. Suffering from persistent groin injuries results in extensive rehabilitation and longstanding pain (Jansen, Mens, Backx, Kolfschoten, & Stam, 2008;Macintyre, Johson, & Schroeder, 2006); as an example, 40% of groin injuries in soccer result in more than one week out, and 10% in more than one month out (Maffey & Emery, 2007).…”
Section: Injury Characteristicsmentioning
confidence: 99%
“…A strain to the groin muscles may be acute but often becomes chronic in nature. Suffering from persistent groin injuries results in extensive rehabilitation and longstanding pain (Jansen, Mens, Backx, Kolfschoten, & Stam, 2008;Macintyre, Johson, & Schroeder, 2006); as an example, 40% of groin injuries in soccer result in more than one week out, and 10% in more than one month out (Maffey & Emery, 2007).…”
Section: Injury Characteristicsmentioning
confidence: 99%
“…Clinical examination identified the dilation of the external inguinal ring, but without a pseudotumoral groin mass. Of a series of 250 athletes who underwent surgery for chronic inguinal pain, only 4% had clear clinical signs of inguinal hernia (Jansen et al, 2008;Campanelli, 2010). Usually, pain had an insidious onset, but it could become bilateral, with some patients also experiencing scrotum pain.…”
Section: Resultsmentioning
confidence: 99%
“…It was interpreted as athletic pubalgia, pubic osteitis, Gilmore hernia, enthesopathy of Ashby's inguinal ligament, so it was considered to be a pubic inguinal pain syndrome (Campanelli, 2010). This syndrome is often found in ball sports, when shear movements or those involving a sudden change of direction are performed, and may originate in any inguinal structure: muscular, tendinous, bone, fascial, nervous, articular (Jansen et al, 2008;Campanelli, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…19 These interventions generally result in a positive outcome for a majority of athletes with longstanding groin pain associated with resisted hip adduction. 18 Researchers have recently shown that wearing a pelvic belt can increase hip adduction strength and decrease pain during resisted hip adduction in athletes with longstanding groin pain associated with resisted hip adduction.…”
Section: Participantsmentioning
confidence: 99%
“…Consequently, treatment is often applied in a nonspecific manner. 19 Longitudinal single-cohort study.…”
mentioning
confidence: 99%